The Effect of Discipline and Competence on Employee Performance with Professionalism as an Intervening Variable - Tri Bastuti Purwantini; Ahmad Juwaini; Anwar Rahim (ITB AAS Indonesia Surakarta, 2023)
This study aims to analyze the influence of the discipline and competence factors on the professionalism and the performance of the Ministry of Agriculture’s ASN employee. The sampling technique carried out in this research is a random sampling with the studied object including 103 ASN appointed in 2018-2020. Data analysis was performed using Structure Equation Modeling (SEM) with the Stata application. The results of the study indicate that employee discipline has a very strong influence on professionalism, either directly or indirectly through employee competence. Competence has a direct effect on the professionalism of ASN employees of the Ministry of Agriculture. Employee professionalism (especially from the indicator variables: 1- working hard and being skilled, 2- loyal and self-potential, 3- commitment in completing tasks, and 4- talent and creativity) has a real positive direct effect on employee performance. An increase in one unit of employee professionalism will increase employee performance by 0.88 units. If the discipline and competence of employees as well as their professionalism increase, the employee's performance will also increase.